2014
DOI: 10.1155/2014/684651
|View full text |Cite
|
Sign up to set email alerts
|

Forgotten DJ Stent with a Large Calculus at Its Distal End in an Ileal Conduit Diversion

Abstract: Calculus formation in an ileal conduit following cystectomy is a known complication. Encrustation and formation of calculus may also occur over a DJ stent retained for a long period; but this is never reported in patients with conduit diversion because of close surveillance of these patients. Here we report first case of a large calculus encrusted over a forgotten DJ stent within an ileal conduit in a man who had undergone urinary diversion following radical cystectomy for carcinoma urinary bladder 8 years ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…In another case report, bilateral staghorn calculus was developed due to forgotten DJ stent in a patient with ileal conduit diversion 6 years back [14]. Similarly, Puri et al reported a large calculus encrusted over a forgotten DJ stent in an ileal conduit patient with urinary diversion 8 years earlier [15].…”
Section: Discussionmentioning
confidence: 94%
“…In another case report, bilateral staghorn calculus was developed due to forgotten DJ stent in a patient with ileal conduit diversion 6 years back [14]. Similarly, Puri et al reported a large calculus encrusted over a forgotten DJ stent in an ileal conduit patient with urinary diversion 8 years earlier [15].…”
Section: Discussionmentioning
confidence: 94%
“…14 16,17 In a case report by Gupta et al, and another by Puri et al, large calculus was developed due to forgotten DJ stent in a patient with ileal conduit diversion. 18,19 Treatment of forgotten DJ stent was indivisualized according to severity of symptoms and radiological findings. In our study, endourological procedure was mostly performed for stent extraction.…”
Section: Discussionmentioning
confidence: 99%